2004
DOI: 10.1038/nm1076
|View full text |Cite
|
Sign up to set email alerts
|

RNAi suppresses polyglutamine-induced neurodegeneration in a model of spinocerebellar ataxia

Abstract: The dominant polyglutamine expansion diseases, which include spinocerebellar ataxia type 1 (SCA1) and Huntington disease, are progressive, untreatable, neurodegenerative disorders. In inducible mouse models of SCA1 and Huntington disease, repression of mutant allele expression improves disease phenotypes. Thus, therapies designed to inhibit expression of the mutant gene would be beneficial. Here we evaluate the ability of RNA interference (RNAi) to inhibit polyglutamine-induced neurodegeneration caused by muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
420
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(429 citation statements)
references
References 24 publications
6
420
1
2
Order By: Relevance
“…6,11,21 However, only a few studies have assessed silencing in patient-derived cells, which exhibit physiologically relevant levels of endogenous expression. 3,[22][23][24][25] We sought to address whether polyQ patient-derived fibroblasts might be a useful model for assessing therapeutic strategies, such as comparing allele-specific and non-allele-specific silencing approaches in genetically accurate cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11,21 However, only a few studies have assessed silencing in patient-derived cells, which exhibit physiologically relevant levels of endogenous expression. 3,[22][23][24][25] We sought to address whether polyQ patient-derived fibroblasts might be a useful model for assessing therapeutic strategies, such as comparing allele-specific and non-allele-specific silencing approaches in genetically accurate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potential of RNA interference (RNAi) based silencing as a therapeutic approach for HD, SCA1, SCA3, SCA6 and SCA7. [2][3][4][5][6][7][8][9][10][11] However, most of these reports have used overexpression models or transgenic animal models to demonstrate efficacy-models which fail to mimic the precise genomic context of mutation found in patients. These models have also failed to provide answers to important questions regarding the necessity and feasibility of allele-specific silencing of the mutant transcript alone, without concomitant silencing of the wild type.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of recombinant AAVs (rAAV) expressing RNAi triggers in the form of shRNAs provided clinical benefit in B05 mice after direct injection into the cerebellar cortex. 5 More recently, we showed that delivery of rAAVs expressing artificial miRNAs directed at mutant ATXN1 mRNA, to the deep cerebellar nuclei (DCN) for transport to PCs and other brainstem neurons, also improved pathologic and behavioral phenotypes in this model. 6 Similarly, rAAVs expressing microRNAs (miRNAs) directed at mutant mouse Atxn1 mRNA was beneficial when applied to the KI SCA1 model.…”
Section: Introductionmentioning
confidence: 98%
“…AAV.shRNA delivery mediates improvements in motor neuron function and in neuronal morphology for at least 21 weeks in murine models of degeneration in the central nervous system. 56,57 Following studies showing that AAV.shRNA delivery reduces Rhodopsin expression in vitro, 58,59 a recent report shows that in vivo expression of a human Rhodopsin transgene can be reduced by up to 90% and that a nonsilenced Rhodopsin gene can be expressed to achieve a degree of rescue. Eyes treated with the suppression-replacement construct showed some preservation of photoreceptors, indicating this approach may be useful in treating dominantly inherited retinal degenerations.…”
Section: Ocular Disease As a Target For Gene Therapymentioning
confidence: 99%